THE LEGAL PROTECTION OF INTELLECTUAL PROPERTY IN TOURISM – A CASE OF TRADE’S AND SERVICES’ MARKS - Lipińska, Izabela (Acta Scientiarum Polonorum. Oeconomia, 2010)
The object of this article is to appear the range and the role of the legal protection of intellectual property considering the tourism and tourist activities. It covers the analysis of statutory, both Polish and European legal instruments in the matter of trade marks (as well as services’ marks) used in this branch. Their appropriate and clear setting may determinate the enterprise’s recognisability, as well as may increase its value on the tourism market. This might be a very important issue regarding the preparation of sport’s international event such as Euro 2012 in Poland.